An objective criterion for determining the South Atlantic Convergence Zone - Ambrizzi, Tércio; Ferraz, Simone E. T. (Frontiers in Environmental Science, 2015)
The South Atlantic Convergence Zone (SACZ) is the dominant summertime cloudiness feature of subtropical South America and the western South Atlantic Ocean, having a significant influence on the precipitation regime of southeastern Brazil. This paper proposes an objective criterion based mainly on precipitation, as this variable is easily obtained on general circulation models simulating past, present and future climate. Usually most SACZ studies use emerging long wave radiation as a precipitation proxy. This is enough to describe event position at first, but using precipitation would allow for better quantification, especially for climate studies, where precipitation is indispensable. An assessment was carried out to find out if classical DJF period is ideal for determining the SACZ for the present climate and future scenarios. In general the SACZ event detection criterion showed quite satisfactory results when event dates were previously known. When it was applied to future climate scenario it identified a number of events compatible with the present climate. The SACZ was well defined for both the simulated and observed precipitation data.